Analisa Perbaikan Mesin Cutting Guna Mengurangi Frekuensi Kerusakan dan Jam Perbaikan Mesin - Pratiwi, Salsa Veby Indah; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The smoothness of the production process in the midst of increasingly tight product competition is one of the important factors that needs to be prioritized, especially in production facilities or machines used for operation. losses for the company in terms of time, costs and reduced machine capacity. So an improvement analysis is carried out by looking at historical data on the cutting machine. This historical analysis can determine corrective and maintenance actions that must be carried out. After carrying out historical analysis, it was found that in 2023 the average percentage of machine damage was 44% with a total downtime of 1115.98 hours and total production of 2541.48 hours. loss amounted to Rp. 132,057,145, while in 2024 the average percentage of damage was 46% with a total downtime of 373.24 hours and total production of 809.33 hours. It is said that the company experienced a production process due to damage to the plong machine amounting to 54% with a total loss amounting to Rp. 65,228,673. Historically this machine is a reference in reducing the frequency and time of damage